Quantitative Analysis Of Community Perceptions About Monkey Conservation In Jambi Province - Anggereini, Evita; Sampurna, Ratu; Anattri, Lega; Syafitri, Viola Amelia; Tommy, Muhamad; Hasanah, Zulfa (Biospecies, 2024)
This research aims to conduct a quantitative analysis of public perceptions regarding monkey conservation efforts in Jambi Province. Monkeys are one of the endangered animal species in the area, and public understanding and support is very important in efforts to preserve them. One of the types of monkeys in Jambi province is wild monkeys which are still disturbing the people of Jambi, especially those close to forests and where many buildings and buildings have been erected. Of course, this makes monkeys lose their habitat and food in nature. In this research, data was collected through results from a Google form involving a total of 89 respondents from various communities in Jambi Province. Quantitative analysis was carried out using various statistical methods to evaluate the level of public awareness and views regarding monkey conservation. It is hoped that the results of this research will provide better insight into public perceptions of monkey conservation and become a basis for developing more effective strategies for their conservation. While awareness and support for monkey conservation in Jambi Province is good, there is still work to be done to effectively protect these species and maintain the sustainability of their ecosystem. Collaborative efforts involving all relevant parties are essential to achieve better conservation goals in the future.